Bimbingan Literasi Media dan Pengarus Utamaan Moderasi Beragama di PPM-PIN IAIN Surakarta (Pascasarjana IAIN Kudus, 2021)
In this Era pf massive digital development, people can acsess information very easily. This can have both possitive and negative effects. The lack of media literacy skills makes people become victims of hoax news and even become victims of provocations from ekstremist community. Throught media literacy skills, internt users can recive the benifits of the media, namely as a means of communication and obtining information. This articleis aim to investigate how PPM-PIN Institut Agama Islam Negeri IAIN Surajarta in vocalize and guide milenial generation (Senior high school students and university students) in developing media literacy capability in effort of religion moderation. In the process, the research use descriptive qualitative. The collecting data of the research apply observation and interview and documentation. The subject in this study were 5 members of the PPM-PIN IAIN Surakarta. Based on the finding of this research, the researcher finds that though literacymedia guidance that is conducted by PPM-PIN IAIN Sureakarta produce education atmosphere whose high religion moderation. As a result, the research is expected can create tolerance in piece lifebetween religious comunity.The output of the religion moderation is creating tolerance life, piece between religious comunity.